(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
Politeness plays a crucial role in intercultural communication as it serves as a bridge between diverse cultures, fostering mutual respect and understanding. Different cultures have varying norms regarding what is considered polite, and being aware of these differences can prevent misunderstandings and conflict. For instance, in some cultures, directness is valued, while others may interpret it as rudeness.